2004
DOI: 10.1091/mbc.e03-06-0430
|View full text |Cite
|
Sign up to set email alerts
|

Nonmuscle Myosin IIA and IIB Have Distinct Functions in the Exocytosis-dependent Process of Cell Membrane Repair

Abstract: Vesicle generation, recruitment, and exocytosis are essential for repairing disruptions of cell membranes. The functions of nonmuscle myosin IIA and IIB in this exocytotic process of membrane repair were studied by the antisense technique. Knockdown of myosin IIB suppressed wound-induced exocytosis and the membrane resealing process. Knockdown of myosin IIA did not suppress exocytosis at an initial wound and had no inhibitory effect on the resealing at initial wounds but did inhibit the facilitated rate of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 57 publications
7
112
0
Order By: Relevance
“…The specificities of these associations have to be established firmly, but they support other studies that have observed that myosin II is functionally required for the final phase of exocytosis. For example, the fusion of lysosomes with the plasma membrane during wound repair depends on myosin IIb 122 . Also, in chromaffin cells, a mutant regulatory myosin light chain decreases docking and exocytosis 123 , and inhibitors of myosin light chain kinase or the myosin ATPase reduce the exocytosis of tear secretory vesicles in lacrimal acinar epithelial cells 124 .…”
Section: Outbound Trafficmentioning
confidence: 99%
“…The specificities of these associations have to be established firmly, but they support other studies that have observed that myosin II is functionally required for the final phase of exocytosis. For example, the fusion of lysosomes with the plasma membrane during wound repair depends on myosin IIb 122 . Also, in chromaffin cells, a mutant regulatory myosin light chain decreases docking and exocytosis 123 , and inhibitors of myosin light chain kinase or the myosin ATPase reduce the exocytosis of tear secretory vesicles in lacrimal acinar epithelial cells 124 .…”
Section: Outbound Trafficmentioning
confidence: 99%
“…Although myosin IIA was the isoform identifi ed as a component of the WIP -WASp -containing multiprotein complex at the synapse by vMALDI tandem mass spectroscopy ( 10 ), a smaller amount of myosin IIB was also seen by Western blot (unpublished data). In this light, nonmuscle myosin IIA and IIB have been shown to have distinct roles in vesicle exocytosis during cell membrane repair in fi broblasts ( 20 ). Myosin IIA had a proposed role in vesicle traffi cking, and IIB in membrane resealing.…”
Section: Inhibition Of Granule Exocytosismentioning
confidence: 99%
“…In Swiss 3T3 cells, M2B-depletion suppressed wound-induced exocytosis and the membrane resealing process (Togo and Steinhardt 2004), an effect not seen following M2A knockdown. Consistent with these observations, S91 melanoma cells (which lack myosin 5a) showed a normal membrane resealing process (Togo and Steinhardt 2004). These results suggest that M2B plays a distinct role in vesicle trafficking.…”
Section: Synaptic Transmission Vesicle Trafficking and Viral Egressmentioning
confidence: 82%
“…For example, migrating growth cones of rat superior cervical ganglion neurons exhibit a differential distribution of M2A and M2B (Rochlin et al 1995), M2B being the more peripheral. M2B is also found to be peripheral to M2A in lamellipodia of motile cultured Xenopus A6 cells (Kelley et al 1996) and in Swiss 3T3 fibroblasts (Togo and Steinhardt 2004). By contrast, when monolayer cultures of bovine aortic endothelial cells migrate into a scratch wound, M2A is found at the leading edge of motile cells whereas M2B is found at the rear, moving the back end forwards (Kolega 1998(Kolega , 2003.…”
Section: Localisation Expression Development Diseasementioning
confidence: 99%
See 1 more Smart Citation